Psychological impact of cancer scale: Turkish validity and reliability study - Bahcecioglu Turan, Gulcan; Karaman, Seda; Aksoy, Meyreme (Baishideng Publishing Group Inc, 2023)
BACKGROUNDIn the diagnosis and treatment of cancer, it is important to evaluate the com-ponents of psychological adjustment. Considering the key role of nurses in providing care to patients, it is important to evaluate patients, to determine high-risk patients and to use tools with acceptable validity and reliability to develop care plans.AIMTo analyze the Turkish validity and reliability of The Psychological Impact of Cancer Scale (PICS).METHODSThis methodological study was conducted with 257 cancer patients admitted to the oncology-haematology clinic and outpatient clinic of a University Hospital between February and October 2021. After the translation process of the scale, content and construct validity were conducted. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) was examined with construct validity, while item analyses and internal consistency analysis were conducted for reliability.RESULTSAnalyses and assessment results showed that the content validity index of the scale was 0.96. In the exploratory factor analysis of the Turkish adaptation study, total variance rate explained was found as 84.98%. Factor loads of all items were between 0.82 and 0.94. It was found that Cronbach Alpha values were between 0.860 and 0.930 and total scale Cronbach Alpha value was 0.844. EFA and CFA showed that Turkish form of 12-item and 4-factor. The Psychological Impact of Cancer Scale was confirmed with no changes to the original scale. CFA revealed good fit indices.CONCLUSIONTurkish PICS is a valid and reliable measurement tool for the evaluation of individual's psychological response to cancer diagnosis and treatment and for being used in clinical practice.
Keywords: Cancer; Patient; Psychological impact; Reliability; Validity